Answer:
Paul
Step-by-step explanation:
Paul earn more than monica. Though he is getting less interest but because of his higher initial amount he is getting more return.
Computing the return of both
Monica return is 100*3.4%= $3.4 in a year
Paul return is 200*%2.2= $4.4 in a year.
Answer:
![-7y](https://tex.z-dn.net/?f=-7y)
Step-by-step explanation:
Our equation is:
![\left(1x-5y\right)-1\left(x+2y\right)](https://tex.z-dn.net/?f=%5Cleft%281x-5y%5Cright%29-1%5Cleft%28x%2B2y%5Cright%29)
First we dritribute
Now we have, ![x-5y-x-2y](https://tex.z-dn.net/?f=x-5y-x-2y)
light terms
and we get ![-7y](https://tex.z-dn.net/?f=-7y)
Answer=60
Since the base of the prism is a right triangle, we can use the pythagorean theorem to solve for x.
a²+b²=c²
plug in the data
a²+24²=30²
a²+576=900
subtract 576 from both sides
a²=324
sq root
a=18
So x=18
The formula for the volume of a triangular prism is...
V=(area of the base)*(height)
V=1/2bh*H where b=base of triangle h=height of triangle, H=height of prism
plug in the data that we know
720=1/2*18*24*H
720=216*H
divide both sides by 216
3 1/3=H
So x=18 and y=3 1/3 or 3.33 repeating
The product of the two
18*3 1/3=60
Answer=60
Answer:
<em>Answer: a = - 12</em>
Step-by-step explanation:
We have here two equations, one 18x + 12y = 36, the other ax - 8y = - 24;
Now if we were to consider making these two equations have a common y co - efficient, we would multiply the top equation by 2, the bottom consecutively by - 3. This would make a standard 24y ;
2 * ( 18x + 12y = 36 ), ⇒ 36x + 24y = 72
+ - 3 * ( ax - 8y = - 24 ) + - 3ax + 24y = 72
As you can see, all terms are equivalent, besides that of the co - efficient of x. Knowing that, it would be ax must be multiplied by - 3 to receive 36x, as the bottom equation is multiplied by - 3, where all terms are equivalent to the top terms;
- 3 * ax ⇒ 36x, - 3 * - 12x = 36x,
<em>Answer: a = - 12</em>